Fabrication and Structural, Mechanical, and Biological Characterization of Vancomycin-Loaded Chitosan-Hydroxyapatite-Gelatin Beads for Local Treatment of Osteomyelitis - Nafiseh Jirofti; Azadeh Shahroodi; Jebreil Movaffagh; Bibi Sedigheh Fazly Bazzaz; Rezvan Yazdian-Robati; Maryam Hashemi (Journal of Mazandaran University of Medical Sciences, 2023)
Background and purpose: Topical antibiotic medication is an alternative method in treatment of local infections, especially osteomyelitis. Currently several biomaterials are used for this purpose. The present study focused on the fabrication and characterization of chitosan and Vancomycin (VCM)-loaded chitosan (CS)-hydroxyapatite (HA)-gelatin (G) bead in treatment of osteomyelitis. Materials and methods: CS/G/HA/VCM scaffold was prepared by cross-linking using ionotropic gelling. The morphological and mechanical properties, loading efficiency and antibacterial properties were investigated and toxicity assay of fabricated structure was also analyzed. Results: The lyophilization reduced the area, environment, and sphericity of beads. CS/G/HA/VCM structure showed smaller area (4.5 mm2) and perimeter (180 µm) compared to other structures. Suitable morphology and porosity in fabricated beads were confirmed by SEM images in CS/G/HA and CS/G structures. Reduction of strength was observed after adding VCM into fabricated structure, but this happened less in CS/G/HA/VCM structure. Release on day 14 was 58% for CS/G/HA/VCM structure. AddingVCM into CS/VCM (1.88 Mpa) and CS/G/VCM (10.46 Mpa) structures decreased the mechanical strength while it increased the mechanical strength in CS/G/HA/VCM (83.21 Mpa) structure. No toxic activity of fabricated structures was seen against NIH 3T3 cells. The results of the antimicrobial activity against Staphylococcus aureus showed that chitosan beads containing VCM (CS/VCM, CS/G/VCM, CS/G/HA/VCM) could significantly inhibit the growth of S. aureus compared to the positive control (VCM 5%)(P<0.001). onclusion: According to current study, the CS/G/HA/VCM structure can be introduced as a promising candidate in treatment of osteomyelitis.